Knockdown of insulin-like growth factor 2 gene disrupts mitochondrial functions in the liver. (14th May 2021) - Gui, Weiwei; Zhu, Yiyi; Sun, Shuiya; Zhu, Weifen; Tan, Bowen; Zhao, Hanxin; Shang, Chengxin; Zheng, Fenping; Lin, Xihua; Li, Hong
Abstract: Even though insulin-like growth factor 2 (IGF2) has been reported to be overexpressed in nonalcoholic fatty liver disease (NAFLD), its role in the progression of NAFLD and the potential mechanism remain largely unclear. Using in vitro models, we found that IGF2 was the key overexpressed gene in steatosis, suggesting a possible association between IGF2 and NAFLD. Interestingly, loss-of-function experiments revealed that inhibition of IGF2 protein impaired mitochondrial biogenesis and respiration. It additionally disrupted the expression changes of mitochondrial fusion and fission-related proteins necessary in maintaining mitochondrial homeostasis. Consistently, IGF2 knockdown reduced the mitochondrial membrane potential and increased the production of reactive oxygen species. Mechanistically, IGF2 regulates mitochondrial functions by modulating the expression of SIRT1 and its downstream gene PGC1α. This research opens a new frontier on the role of IGF2 in energy metabolism, which potentially participates in the development of NAFLD. As such, IGF2 is a potential therapeutic target against NAFLD.